Important Ways in Designing Vocational Secondary School Teacher Development Education and Training. Issue 1 (January 2021) - Kholis, N; Supriyadi, E; Mardapi, D
Abstract: A mid-level labor preparation having the qualification and competency appropriate with working world needs is a task from vocational secondary school (VSS). Now days, VSS become an attention by wide community, as a result of the existence of government policy which is trying to empowering vocational secondary education. The policy taken is by performing the revitalization of vocational school which has the aim to improve the quality of labor competitiveness. One of the programs is teacher quality improvement through various teacher training. However, relating to this case, it is suspected that the previous vocational school teacher training is less effective, so that it needs to be conducted the analysis about the teacher training implementation. Therefore, this article will be elaborated the ways needed to be conducted in improving the educational quality and vocational school teacher development training. The ways should be considered when it is planned and implemented the effective training program, such as: determining the needs, setting the goal, determining the content of learning, selecting the participants, determining the best schedule, selecting the appropriate facilities, selecting the proper instructor, selecting and preparing the audiovisual equipment, coordinating the program and evaluating the program.